The Relaxing Effect of α-Defensin 1 on the Adrenergic Responses of Rat Bladder - Lee, Shin Young (The Korean Physiological Society and The Korean Society of Pharmacology, 2011)
Defensins, cysteine-rich cationic polypeptides released from neutrophils, are known to have powerful antimicrobial properties. In this study, we sacrificed 30 rats to investigate the effects of α-defensin 1 on detrusor muscle contractions in isolated rat bladder. From the experiments we found relaxing effects of α-defensin 1 on the contractions induced by phenylephrine (PE) but not by bethanechol (BCh) in the detrusor smooth muscles. To determine the mechanisms of the effects of α-defensin 1, the changes of effects on PE-induced contraction by α-defensin 1 pretreatment were observed after pretreatment of Rho kinase inhibitor (Y-27632), protein kinase C (PKC) inhibitor (Calphostin C), potent activator of PKC (PDBu; phorbol 12,13-dibutyrate), and NF-κB inhibitors (PDTC; pyrrolidinedithiocarbamate and sulfasalazine). The contractile responses of PE (10(-9)~10(-4) M) were significantly decreased in some concentrations of α-defensin 1 (5×10(-9) and 5×10(-8) M). When strips were pretreated with NF-κB inhibitors (PDTC and sulfasalazine; 10(-7)~10(-6) M), the relaxing responses by α-defensin 1 pretreatment were disappeared. The present study demonstrated that α-defensin 1 has relaxing effects on the contractions of rat detrusor muscles, through NF-κB pathway. Further studies in vivo are required to clarify whether α-defensin 1 might be clinically related with bladder dysfunction by inflammation process.